Isolation, Prevalence And Antibiotic Resistance Of Salmonella Spp. In Fish Obtained From Wet Markets In Penang, Malaysia - Lim, Jia Her (Universiti Sains Malaysia, 2020)
Salmonella is the foodborne pathogen that can cause infection to human. The main reservoir of Salmonella is usually associated with poultry and poultry products. Fish can be the source of human infection if the fish product are contaminated through the aquatic environment and post-harvest handling. However, insufficient information is reported on the occurrence of Salmonella from fish in Malaysia. The aim of this study was to isolate Salmonella spp. from fish sold at wet markets in Penang, Malaysia and determine its antimicrobial susceptibility profiles. Isolation of Salmonella spp. from fish samples was performed using ISO-6579-1 bacteriological procedures. The isolates were confirmed through biochemical test and serotyped by slide agglutination test. Susceptibility of the isolates to 8 antimicrobials was conducted using Kirby-Bauer disk diffusion method according to the guidelines of the Clinical and Laboratory Standards Institute (CLSI). A total of 30 fish samples (freshwater and seawater fish) were selected randomly from 3 wet markets in Penang, Malaysia. A total of 13 (43.3%) fish samples were positive for Salmonella. Freshwater fish (66.7%) has a higher contamination rate than seawater fish (27.8%). All Salmonella isolates investigated were resistant to at least four antibiotics. High resistance rate (100%) was recorded to ampicillin, amoxicillin-clavulanic acid, tetracycline and kanamycin. Isolate CY01, CY02 and SZ02 exhibited the highest multiple antibiotic resistance (MAR) index value of 0.86 which showed resistance to six antibiotics. Emergence of such multidrug resistant strains of Salmonella from fish is a potential serious threat to global public health. Difficulties in controlling the rise of antibiotic resistance are likely to cause adverse side effects to both human beings and animals.